The Effectiveness of Virtual Reality and Augmented Reality Implementation in Improving Vocational Education Practical Skills: A Meta-Analysis Study - Muhammad Akbar; Nurhasan Syah; M Giatman; Dedy Irfan; Hansi Effendi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
(AR) and (VR) are considered effective educational tools for promoting meaningful learning processes, increasing student engagement, and encouraging active participation. However, there are still differences of opinion among academics regarding the extent to which these learning media actually help students develop their practical skills. Using a meta-analysis methodology, this study aims to thoroughly examine the effectiveness of using (VR) and (AR) in improving practical skills in vocational education. The PRISMA approach, which includes identification, screening, and inclusion steps, was used to screen scientific publications published in the last five years (2020–2025) that were accessible through Google Scholar and SCOPUS. The field of research and year of publication were the basis for the inclusion criteria. Of the 546 items found, 6 were eligible for analysis. Significance tests and effect size calculations were used to analyze the data. With an effect size of 0.754 and a p-value of 0.025 < 0.05, the meta-analysis findings indicate that the use of VR and AR has a moderate impact on improving practical skills and is free from potential data bias. These findings have important implications for educators and policymakers who wish to use VR and AR as crucial teaching and learning techniques.